Quantitation of Hydrogen Peroxide Fluctuations and Their Modulation of Dopamine Dynamics in the Rat Dorsal Striatum Using Fast-Scan Cyclic Voltammetry - Spanos, Marina (American Chemical Society, 2013)
[Image: see text] The dopaminergic neurons of the nigrostriatal dopamine (DA) projection from the substantia nigra to the dorsal striatum become dysfunctional and slowly degenerate in Parkinson’s disease, a neurodegenerative disorder that afflicts more than one million Americans. There is no specific known cause for idiopathic Parkinson’s disease; however, multiple lines of evidence implicate oxidative stress as an underlying factor in both the initiation and progression of the disease. This involves the enhanced generation of reactive oxygen species, including hydrogen peroxide (H(2)O(2)), whose role in complex biological processes is not well understood. Using fast-scan cyclic voltammetry at bare carbon-fiber microelectrodes, we have simultaneously monitored and quantified H(2)O(2) and DA fluctuations in intact striatal tissue under basal conditions and in response to the initiation of oxidative stress. Furthermore, we have assessed the effect of acute increases in local H(2)O(2) concentration on both electrically evoked DA release and basal DA levels. Increases in endogenous H(2)O(2) in the dorsal striatum attenuated electrically evoked DA release, and also decreased basal DA levels in this brain region. These novel results will help to disambiguate the chemical mechanisms underlying the progression of neurodegenerative disease states, such as Parkinson’s disease, that involve oxidative stress.